Attitudes for records management in Carigali-Pttepi Petroleum, Malaysia/ Ana Shazreen Abu Bakar...[et.al] - Abu Bakar, Ana Shazreen; Jaafar, Nur Hidayah; Ahmad, Siti Solehah; Abdul Wahab, Siti Nursyahirah (2015)
Records are become essential in order to become an evidence for future used. The management of the records in an organization needs to be more focused and appropriate, so that the value of the records can be maintained and preserved. Records management practice is a 'policy' that all records have to follow in order to standardize the records management system. Therefore, all organization has to cooperate in managing their records by following the policy, act and procedure that have been set. Records management should be supported with corporate policy, adoption of records management standards, skilled people and streamlining storage for an organization to undertake to strengthen the management of their records to respond to customer.